2019
DOI: 10.1158/0008-5472.can-18-2110
|View full text |Cite
|
Sign up to set email alerts
|

Retrodifferentiation of Human Tumor Hepatocytes to Stem Cells Leads to Metabolic Reprogramming and Chemoresistance

Abstract: Human hepatocellular carcinoma (HCC) heterogeneity promotes recurrence and therapeutic resistance. We recently demonstrated that inflammation favors hepatocyte retrodifferentiation into progenitor cells. Here, we identify the molecular effectors that induce metabolic reprogramming, chemoresistance, and invasiveness of retrodifferentiated HCC stem cells. Spheroid cultures of human HepaRG progenitors (HepaRG-Spheres), HBG-BC2, HepG2, and HuH7 cells and isolation of side population (SP) from HepaRG cells (HepaRG-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…In line with other works [49,50], the spheroidal culture showed passage-dependent phenotypic and molecular changes and displayed multiple features of stemness properties tested, including up-regulated expression of pluripotency factors, enhanced self-renewal, cell migration and invasion abilities, and multi-lineage differentiation (Figures 1 and 2). Chemoresistance to 5-FU and oxaliplatin was enhanced in increasing passages of the spheroid cells, further supporting CSC enrichment in the spheroids (Figure 2F,G), as has also been reported for CRC and other cancers [51][52][53]. The ability of the cells to differentiate into ectodermic and mesodermic lineages supported the pluripotency of the CSC in the spheroids, as was also reported for CRC cancer stem cell-like population to differentiate into mucin-producing goblet cells, enterocyte-like and neuroendocrine-like cells [18].…”
Section: Discussionsupporting
confidence: 84%
“…In line with other works [49,50], the spheroidal culture showed passage-dependent phenotypic and molecular changes and displayed multiple features of stemness properties tested, including up-regulated expression of pluripotency factors, enhanced self-renewal, cell migration and invasion abilities, and multi-lineage differentiation (Figures 1 and 2). Chemoresistance to 5-FU and oxaliplatin was enhanced in increasing passages of the spheroid cells, further supporting CSC enrichment in the spheroids (Figure 2F,G), as has also been reported for CRC and other cancers [51][52][53]. The ability of the cells to differentiate into ectodermic and mesodermic lineages supported the pluripotency of the CSC in the spheroids, as was also reported for CRC cancer stem cell-like population to differentiate into mucin-producing goblet cells, enterocyte-like and neuroendocrine-like cells [18].…”
Section: Discussionsupporting
confidence: 84%
“…A study showed that nANGPTL4 is an orphan ligand that mainly controls lipid metabolism and cANGPTL4 binds-e.g., β-integrins, VE-cadherin, and claudin-5-to induce vascular leakage and tumor progression [19]. An increasing number of studies have indicated the possible involvement of ANGPTL4 in the development of cardiovascular diseases [20][21][22], inflammatory diseases [23][24][25][26], cancers [27][28][29], etc. However, there are still no reports on the role of ANGPTL4 in bacterial meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…However, SR HCC is causally linked to the maintenance of stem-like properties [27]. Enriched spheres with SR signatures have been related to CSCs, metastasis, and recurrence of HCC [28]. These findings provide us with confidence in defining the correlation between expression significantly inhibited SR cells by reducing apoptosis through the AKT/ERK pathway [31] and tumor-initiating cell phenotypes [32].…”
Section: Discussionmentioning
confidence: 81%